GTP hydrolysis controls stringent selection of the AUG start codon during translation initiation in Saccharomyces cerevisiae - Huang, Han-kuei (Cold Spring Harbor Laboratory Press, 1997)
We have isolated and characterized two suppressor genes, SUI4 and SUI5, that can initiate translation in the absence of an AUG start codon at the HIS4 locus in Saccharomyces cerevisiae. Both suppressor genes are dominant in diploid cells and lethal in haploid cells. The SUI4 suppressor gene is identical to the GCD11 gene, which encodes the γ subunit of the eIF-2 complex and contains a mutation in the G(2) motif, one of the four signature motifs that characterizes this subunit to be a G-protein. The SUI5 suppressor gene is identical to the TIF5 gene that encodes eIF-5, a translation initiation factor known to stimulate the hydrolysis of GTP bound to eIF-2 as part of the 43S preinitiation complex. Purified mutant eIF-5 is more active in stimulating GTP hydrolysis in vitro than wild-type eIF-5, suggesting that an alteration of the hydrolysis rate of GTP bound to the 43S preinitiation complex during ribosomal scanning allows translation initiation at a non-AUG codon. Purified mutant eIF-2γ complex is defective in ternary complex formation and this defect correlates with a higher rate of dissociation from charged initiator-tRNA in the absence of GTP hydrolysis. Biochemical characterization of SUI3 suppressor alleles that encode mutant forms of the β subunit of eIF-2 revealed that these mutant eIF-2 complexes have a higher intrinsic rate of GTP hydrolysis, which is eIF-5 independent. All of these biochemical defects result in initiation at a UUG codon at the his4 gene in yeast. These studies in light of other analyses indicate that GTP hydrolysis that leads to dissociation of eIF-2 ⋅ GDP from the initiator-tRNA in the 43S preinitiation complex serves as a checkpoint for a 3-bp codon/anticodon interaction between the AUG start codon and the initiator-tRNA during the ribosomal scanning process.